Assessing the Efficiency of Green Absorbent in Treating Nutrients and Heavy Metal in Wastewater - Chow M.F.; Bahruddin A.S.; Chua K.H. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study is aimed to determine the performances of zeolite-water hyacinth ash (WHA)-clay (ZWC) pellets on removing nutrients (nitrogen (N) and phosphorus (P)) and heavy metal (HM). In this study, the adsorption experiments were conducted for various pellet compositions and sizes, the application of pre-treatment on pellets, and tested with different concentrations of synthetic wastewater. The results identified that the maximum removal capacities of ZWC pellet were 0.112 mg/g, 0.08 mg/g, 0.171 mg/g, and 0.151 mg/g for phosphate (PO4), total phosphorus (TP), nitrate-nitrogen (NO3), and total nitrogen (TN), respectively. The optimization experiment indicated that smaller pellet sizes and those treated with calcium hydroxide solution exhibited better N&P and HM removal performances. The optimized ZWC pellet was able to remove up to 90%, 86%, 94%, 90%, 84%, 86%, and 91% for PO4, TP, NO3, TN, zinc (Zn), copper (Cu), and lead (Pb), respectively, after 3 h of contact time. The ZWC pellet proved that it can be used as an effective adsorbent for wastewater treatment. 2023 by the authors.